CENTRAL ASIA: ECONOMIC COOPERATION POTENTIAL - RAKHMATULLINA, Gulnur (CENTRAL ASIA AND THE CAUCASUS, 2007)
The Central Asian republics are rich in energy resources: three of them (Kazakhstan, Uzbekistan, and Turkmenistan) can boast of oil and gas deposits, while the other two (Kyrgyzstan and Tajikistan) have vast hydropower potential. This means that harmonized energy policy designed to meet their demands in energy, energy exports, and stronger positions in ensuring international energy security makes sense. By the same token, these countries can, potentially, develop metallurgy, machine building, and light industry as their industrial priorities. In fact, deeper integration in these fields will add efficiency to their efforts to fully tap the region’s industrial potential. Integration in the agricultural sector with a view to developing, some time in the future, the common agrarian market is another local priority. Transport is the field in which integration is even more welcome: the region’s transit potential will expand the trade and economic ties among the local states and revive the Great Silk Road. The present level of mutual trade has not yet reached the highest possible level of economic cooperation: the share of its Central Asian neighbors in Kazakhstan’s trade turnover is about 0.6 percent (in 2006, Kyrgyzstan’s share in Kazakhstan’s trade turnover was a meager 0.7 percent; Tajikistan’s share, 0.3 percent; Uzbekistan’s, 1.1 percent, and Turkmenistan’s, 0.2 percent). This means that deeper regional integration has become a priority and a factor of the local countries’ faster economic growth, higher living standards, and stability.